Charge discharge characteristics of normal and nano LiNi₁₋ₓC₀ₓO₂ / Nor Suriayati Mustapa - Mustapa, Nor Suriayati (2011)
Lithium nickel cobalt oxide (LiNi₁₋ₓC₀ₓO₂) issued a high capacity method material in the fabrication of a bi-cell type of lithium ion polymer battery (LIPB). The capacity and cycle performance of the battery is evaluated from the charge discharge characteristics. LiNio.7Coo.3O2 prepared via Ball Milling (BM) by annealing temperature for 3 hours is displays a higher initial discharges capacity (180mAh/g) than the LiNio.7Coo.3O2 for 12 hours .The charges - discharge characteristics and performance of the battery at the room temperature are evaluated to ascertain the effective viability. The value of capacity depend on the sample. When increased the cobalt, the capacity is decreased. The electrochemical analysis reveal that the discharge capacity of LiNi₁₋ₓC₀ₓO₂ significantly depends on the particle size. The relation between structural and electrochemical properties used in advanced rechargeable lithium battery.